Contributions of pyrolysis, volatile reforming and char gasification to syngas production during steam gasification of raw and torrefied leftover rice. (15th November 2021) - Huang, Jingchun; Feng, Chao; Yu, Yun; Xie, Di; Wang, Zhenqi; Hu, Wei; Qiao, Yu
Highlights: Contributions of gasification stages are studied for raw/torrefied leftover rice. Gas formation is dominantly contributed by pyrolysis for raw sample. Char gasification dominates gas formation for torrefied sample at high temperatures. Char gasification reaction to CO2 is significantly enhanced at high temperatures. Abstract: Steam gasification generally involves three main stages including pyrolysis, volatile reforming and char gasification. This study carries out the experiments from each gasification stage of leftover rice at 600–1000 °C, using a novel two-stage pyrolysis/gasification reactor system. The gas and tar products from different gasification stages of raw and torrefied leftover rice are characterized and compared to understand the contributions of different gasification stages to syngas production. It is found that the raw leftover rice can be completely cracked into volatile products at 600 °C during the pyrolysis stage, generating high yields of tar (21.1%) and gas (69.2%). The tar yield reduces greatly as the pyrolysis temperature increases to 700 °C, leading to a high cold gas efficiency (CGE) of 88.1%. A further increase in the pyrolysis temperature leads to a reduction in the CGE due to increased coke formation. The results also show that the presence of steam has negligible effect on the cracking/reforming of volatiles, thus gas is dominantly generated during the pyrolysis stage at all temperatures. In contrast, the torrefied leftover rice generates much lower gas yields at all pyrolysis temperatures. Compared to the tar yields for the raw sample, the tar yield for the torrefied sample at 600 °C (13.2%) is lower, but becomes higher at high temperatures. The pyrolysis stage also significantly contributes to the gas formation at low temperatures (i.e., ≤800 °C). A further increase in gasification temperature to 1000 °C largely enhances the char gasification reactions (especially for the reaction to form CO2 ), leading to a large increase in the contribution of the char gasification stage to the gas formation (i.e., 7.7% at 600 °C to 70.6% at 1000 °C). This study will provide key data for the design of suitable gasification reactors for the raw and the torrefied food wastes.